Digital economy, peer influence, and persistent green innovation of firms: a mixed embeddedness perspective - Jiafeng Gu (Environmental Science and Pollution Research, 2024)
Persistent green innovation helps enterprises save energy, reduce pollution, and continue to gain economic benefits. However, existing studies explored the economic and organizational factors influencing firms’ persistent green innovation while neglecting peer influence in the digital economy. This study examines the impact of digital economy and peer influence on persistent green innovation using data of Chinese-listed companies from 2011 to 2019. The results show that digital economy and peer influence positively affect persistent green innovation. Moreover, digital economy plays a competitive mediating role between peer influence and persistent green innovation. The results of further research show that both the time lag term of peer influence and spatial lag term of digital economy affect persistent green innovation. This study incorporates the three-level elements of enterprise, peer, and city into a unified framework, providing theoretical reference and practical guidance for green innovation to enhance the competitive advantage of enterprises.